GAYA BAHASA BERDASARKAN LANGSUNG TIDAKNYA MAKNA DALAM PANTUN ADAT JAMBI: KAJIAN STILISTIKA - Priyanto Priyanto (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2016)
ABSTRACT The purpose of this study is to describe the style of language based on the directness of the meaning contained in the traditional pantun Jambi. The method used in this research is descriptive qualitative method, with stilistika approach. The data in this study is the style of figurative language which is the scope of stylistic analysis. The data source in the research is the rhyme contained in the book "Principles of Traditional Shoot Jambi Nine Village Head Jilid III Customary Literature Jambi". The style of language based on the directness of the meaning found in the Jambi customary pantun is: (1) the rhetorical language style, which includes (a) the euphemismus or euphemism style, (b) the style of the asonance language, (c) the language style of pleonasme and tautology; ) the alliterational style of language, and (2) the figurative style of language which includes (a) the style of the metaphorical language, (b) the language style of personification, (c) the language style of the sinekdoke, (d) the language of irony. The conclusion of this research is the style of language based on the directness of the dominant meaning that is used is rhetorical style and figurative language style. Keywords: style of language based on the directness of meaning, pantun Adat Jambi